2019
DOI: 10.3390/rs11161915
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Ground-Point Classifiers for Terrestrial LiDAR

Abstract: Previous literature has compared the performance of existing ground point classification (GPC) techniques on airborne LiDAR (ALS) data (LiDAR—light detection and ranging); however, their performance when applied to terrestrial LiDAR (TLS) data has not yet been addressed. This research tested the classification accuracy of five openly-available GPC algorithms on seven TLS datasets: Zhang et al.’s inverted cloth simulation (CSF), Kraus and Pfeiffer’s hierarchical weighted robust interpolation classifier (HWRI), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…A case from Guelph, Canada illustrated the performance of several ground-point classification algorithms using different features of interest (e.g., low vegetation, high vegetation). Interestingly, the cloth simulation filter (CSF) algorithm had the highest accuracy for high vegetation (forest type), producing a kappa of 0.844 [ 28 ]. In another study, Corte et al [ 29 ] classified ground and off-ground points using the progressive TIN densification filtering technique available in LAStools for generating a DTM and digital surface model (DSM); they used a resolution of 0.5 m to extract total tree height.…”
Section: Introductionmentioning
confidence: 99%
“…A case from Guelph, Canada illustrated the performance of several ground-point classification algorithms using different features of interest (e.g., low vegetation, high vegetation). Interestingly, the cloth simulation filter (CSF) algorithm had the highest accuracy for high vegetation (forest type), producing a kappa of 0.844 [ 28 ]. In another study, Corte et al [ 29 ] classified ground and off-ground points using the progressive TIN densification filtering technique available in LAStools for generating a DTM and digital surface model (DSM); they used a resolution of 0.5 m to extract total tree height.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Nakano et al [ 9 ], Ravi et al [ 17 ] and Péntek et al [ 18 ] have performed fundamental analysis of lidar performance for various detection tasks, while Roberts et al [ 19 ], Azevedo et al [ 20 ] and Gilhuly and Smith [ 21 ] investigated the capability of UAV-mounted lidar in classifying ground points, detecting power lines, and terrain mapping, respectively. Additionally, Kandath et al [ 22 ] have shown the viability of incorporating sensor information from a low-flying UAV into UGV path planning algorithms.…”
Section: Related Workmentioning
confidence: 99%
“…The following formulas correspond to the performance metrics (e.g. Xia and Wang, 2017;Roberts et al, 2019) that were calculated from a confusion matrix of classified ground and non-ground points (abbreviations refer to Table 1):…”
Section: Validation Proceduresmentioning
confidence: 99%
“…Extracting the points that represent the terrain in a 3D point cloud has a long tradition (e.g. Kraus and Pfeifer, 1998) and a variety of techniques and tools have been proposed and evaluated to achieve this (Sithole and Vosselman, 2004;Chen et al, 2017;Roberts et al, 2019). The general principle of terrain filtering is to select those points which represent the bare earth and remove objects in the intervening space.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation